Investigating Vocational High school Teachers’ Challenges in Integrating Computer Assisted Instruction (CAI) into EFL Classes - Lubis, Nur Halimah; Fithriani, Rahmah (Jurnal Paedagogy, 2023)
This study aims to identify and investigate the difficulties encountered by English teachers utilizing Computer-Assisted Instruction (CAI) in a vocational high school in Mandailing Natal, North Sumatra. This research used a qualitative descriptive method, in which description was used to analyze and interpret data. Six school English teachers were interviewed and observed during their classroom practice. The collected data were analyzed using coding techniques. The findings of this study indicated that English teachers continued to confront numerous obstacles and difficulties in their instruction, particularly regarding the use of technology. This difficulty arose for several reasons, spanning from the need to invest a substantial amount of time to increase technological skill to the absence of adequate technological resources and support. Therefore, schools must focus on rectifying facility deficiencies, particularly in technology and other facilities that support instruction. Teachers and Educators must also be capable of judiciously utilizing available technology to implement simplified methods optimally.